Prosecuting Domestic Violence Cases with Reluctant Victims in Milwaukee, Wisconsin, 1994-1995 - Davis, Robert C. ([Verlag nicht ermittelbar], 2006)
Officials in Milwaukee, Wisconsin, introduced two experiments designed to provide answers to questions of how to deal with victim reluctance in domestic violence cases. Two projects funded by the National Institute of Justice (NIJ) evaluated these Milwaukee domestic violence experiments. The first project examined the effectiveness of a specialized domestic violence court that opened in September 1994. The primary intent of the specialized domestic violence court was to speed up the disposition of cases. The second project examined the impact of a change in the district attorney's (DA's) screening policy that admitted more cases into the special court, which became effective January 1, 1995. The liberalized prosecutorial policy was intended to determine whether arrests that the DA normally rejected for prosecution because victims failed to attend the prosecutor's charging conference could be prosecuted successfully none the less. The researchers collected data from three time periods: (1) prior to September 1994, (2) between September 1994 and January 1995, and (3) post-Janurary 1995. For the first experiment, several samples were selected from court and DA records to assess the impact of the introduction of the special domestic violence court and its impact after the change in the DA's charging policy. These samples of domestic violence cases (court samples) filed by the prosecutor included: (1) 237 cases from Summer 1994, (2) 190 cases from Fall 1994, and (3) 242 cases from Spring 1995. For the second experiment, three additional samples (complaint room samples) were collected of domestic cases declined by the prosecutor to determine how victim attendance at the charging conference and other factors affected the decision to prosecute: (1) 152 cases from Summer 1994, (2) 155 cases from Fall 1994, and (3) 152 cases from Spring 1995. Variables in this dataset include if the case was filed, type of charges, number of prior misdemeanors, number of prior felonies, number of misdemeanors after, number of felonies after, number of felony convictions, number of misdemeanor convictions, number of subpoenas, number of judicial body attachment orders, whether the victim was cooperative, if the victim testified, method of disposition, type of disposition, time to disposition, time to sentencing, sentencing conditions, if the defendant received jail or prison time, if the defendant received probation time, number of months incarcerated, number of months on probation, and several date variables. Additional variables provide the sex of the defendant, the relationship between the defendant and the victim, if the victim was injured, if the victim was intoxicated, and use of a weapon.